2018
DOI: 10.7759/cureus.3659
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: An Indicator of Complicated Gall Stone Disease?

Abstract: BackgroundGallstone disease is a common surgical entity worldwide and accounts for a major portion of hospital admissions and surgeries. Metabolic syndrome is diagnosed when three of the following medical conditions are positive: central obesity, high blood pressure, increased fasting glucose levels, low high-density lipoprotein (HDL) levels and high serum triglycerides.ObjectiveTo compare the frequency of metabolic syndrome in patients with uncomplicated gallstone disease and complicated gallstone disease.Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
1
0
3
Order By: Relevance
“…Metabolic syndrome was more predominant in CGSD in compare to UGSD. 20,21 We found that presence of metabolic syndrome (p<.05) is an independent predictor of CGSD after applying logistic regression analysis and Wald criteria. Metabolic syndrome was presented in 58.2% patient of CGSD group and 21.8% patients of UGSD patients, which was statistically significant (OR 4.986, CI 2.763-8.995, p value <0.001) Sanchez NM et al, studied that total metabolic syndrome was associated with a more than three-fold risk of gallstone disease (OR = 3.20; 95%CI, 1.71-6.01; P = 0.0001).…”
Section: Discussionmentioning
confidence: 86%
“…Metabolic syndrome was more predominant in CGSD in compare to UGSD. 20,21 We found that presence of metabolic syndrome (p<.05) is an independent predictor of CGSD after applying logistic regression analysis and Wald criteria. Metabolic syndrome was presented in 58.2% patient of CGSD group and 21.8% patients of UGSD patients, which was statistically significant (OR 4.986, CI 2.763-8.995, p value <0.001) Sanchez NM et al, studied that total metabolic syndrome was associated with a more than three-fold risk of gallstone disease (OR = 3.20; 95%CI, 1.71-6.01; P = 0.0001).…”
Section: Discussionmentioning
confidence: 86%
“…Длительное время среди врачей существовало мнение о том, что золотым стандартом лечения ЖКБ является лапароскопическая холецистэктомия. В мировой практике по числу оперативных вмешательств холецистэктомия, проведенная по поводу ЖКБ, занимает второе место после аппендэктомии [1,5]. В США выполняется более 700 тысяч таких операций ежегодно [4].…”
Section: The High Prevalence Of Metabolic Syndrome In Population Has unclassified
“…Но, несмотря на это, даже при адекватном и рациональном отборе пациентов эффективность лечения ЖКБ с использованием УДХК достигает 70 % [3,4,5,32]. Учитывая тот факт, что сама терапия является длительной и дорогостоящей, особо актуальным представляется вопрос об уточнении показаний к ее проведению, а также о разработке способов прогнозирования эффективности предстоящего консервативного лечения.…”
Section: The High Prevalence Of Metabolic Syndrome In Population Has unclassified
See 1 more Smart Citation